2018
DOI: 10.1002/cbic.201700574
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Templated Concatenation of Triplet Nucleic‐Acid Probe

Abstract: Template-directed synthesis offers several distinct benefits over conventional laboratory creation, including unsurpassed reaction rate and selectivity. Although it is central to many biological processes, such an approach has rarely been applied to the in situ synthesis and recognition of biomedically relevant target. Towards this goal, we report the development of a three-codon nucleic-acid probe containing a C-terminal thioester group and an N-terminal cysteine that is capable of undergoing template-directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…This strategy hasbeen used to target the rCAG-repeat expansion associated with Huntington's disease and a number of other related neuromuscular and neurodegenerative disorders (Figure 4d). 21,104 A supramolecular approach has also been reported to target repeat sequences. In this case, slightly longer PNA probes (6-mer) functionalized with pyrene moieties that can stabilize adjacent probe hybridization through stacking interactions were shown to be sufficient to disrupt a pathogenic interaction between the rCUGexpansion sequence and MBL1 complex.…”
Section: 103mentioning
confidence: 99%
“…This strategy hasbeen used to target the rCAG-repeat expansion associated with Huntington's disease and a number of other related neuromuscular and neurodegenerative disorders (Figure 4d). 21,104 A supramolecular approach has also been reported to target repeat sequences. In this case, slightly longer PNA probes (6-mer) functionalized with pyrene moieties that can stabilize adjacent probe hybridization through stacking interactions were shown to be sufficient to disrupt a pathogenic interaction between the rCUGexpansion sequence and MBL1 complex.…”
Section: 103mentioning
confidence: 99%
“…Further, short PNA probes (9-14 mer) designed to target double-stranded RNA forming a PNA:RNA2 triplex [34][35][36] and selectively target the mRNA sequence of HOTAIR gene for cancer therapy have been developed [37]. Similarly, we have developed short PNA probes (3mer) to target the double-stranded CUG triplet repeat-containing hairpin RNAs in vitro [38]. Although the aforementioned short oligonucleotide probes can bind to target RNAs, few issues related to specificity, sequence selection, delivery and in vivo validation have not yet been completely resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The cystine group was employed to provide greater control in probe handling. Prior studies revealed that a ligand of the same length comprising all natural nucleobases has a reduced (acyclic) half-life of ∼1 h at a physiological temperature (37 °C) . We expected a similar half-life for LG2N*.…”
Section: Resultsmentioning
confidence: 71%
“…LG2N* has a half-life of ~3 h, which is ~3 times longer than that of the natural counterpart. 75 We attributed the chemical stability of LG2N* to the expanded aromatic ring size of the E base, which provides better base-stacking interaction and, thus, makes ligand less conformation-ally flexible.…”
Section: Resultsmentioning
confidence: 98%